2013
DOI: 10.1080/00918369.2013.806179
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Identity in the American Deep South: The Concordance and Discordance of Sexual Activity, Relationships, and Identities

Abstract: This research explores the association between sexual identity and sexual behavior and how that association varies across gender and race in the American Deep South. Multinomial logistic regression analysis is used to determine the likelihood of each sexual identity given past sexual behavior, sexual relationships, and other social characteristics. The more traditional cultural climate of the South appears to suppress identification as a sexual minority. Sexual identification in the Deep South is primarily a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Disadvantaged group status helps explain why women, racial minorities, and sexual minorities are more liberal, and identity affirmation and acculturation processes can help explain why sexual minorities are more consistently liberal than other disadvantaged groups. Similar to the distinction between having interracial parents and identifying as biracial (Davenport 2016), there is a distinction between being attracted to people of the same gender and affirmation of a sexual minority identity (Armstrong 2002;Baunach and Burgess 2013;Brown-Saracino 2015). Identity explanations, such as identity affirmation (Egan 2012) and acculturation (Lewis et al 2011), emphasize the importance of identity in a process moving from affirmation of a marginalized identity, subsequent intra-group contact, increasing group commitment, and, finally, attitudinal assimilation and cohesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disadvantaged group status helps explain why women, racial minorities, and sexual minorities are more liberal, and identity affirmation and acculturation processes can help explain why sexual minorities are more consistently liberal than other disadvantaged groups. Similar to the distinction between having interracial parents and identifying as biracial (Davenport 2016), there is a distinction between being attracted to people of the same gender and affirmation of a sexual minority identity (Armstrong 2002;Baunach and Burgess 2013;Brown-Saracino 2015). Identity explanations, such as identity affirmation (Egan 2012) and acculturation (Lewis et al 2011), emphasize the importance of identity in a process moving from affirmation of a marginalized identity, subsequent intra-group contact, increasing group commitment, and, finally, attitudinal assimilation and cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is a marginalized identity often fraught with social costs, especially for those embedded in conservative social contexts, sexual minority identity could be a particularly strong predictor of social attitudes (Egan 2012). People from more progressive backgrounds can be more likely to affirm a sexual minority identity, and the experience of recognizing and affirming that identity could shape sexual minorities' social outlook (see Baunach and Burgess 2013;Brown-Saracino 2015;Wedow et al 2017 on affirmation of sexual minority identity).…”
Section: Argument and Expectationsmentioning
confidence: 99%
“…Most studies, albeit those conducted in the US, find that, despite improvements (Keleher and Smith, 2012), black men maintain elevated rates of homophobia compared to white (Baunach and Burgess, 2013), something that Southall et al (2011) found when comparing the attitudes of white versus black football players in the American South. This differential has been theorized to reflect disproportionately higher rates of blacks in lower economic classes and, as a way to raise their own worth by saying, “at least I’m not gay” (Froum, 2007).…”
Section: Theorizing Masculinities Race and Religionmentioning
confidence: 99%
“…To date, studies have examined how context and environment influences sexual activity, sexual identity, and support for marriage equality, but the studies have lacked analyses of migration patterns. For instance, Baunach and Burgess (2013) found that sexual activity and relationships were important predictors of sexual identification in the South, more so than in other areas of the country. Their findings suggest that individuals with rural and southern backgrounds at age 12 are less likely to identify as bisexual or homosexual and sexual activity, relationships, and identification tend to be in accordance.…”
Section: Migrationmentioning
confidence: 99%